THE EFFECT OF LINE DRAWING IN TEACHING ENGLISH VOCABULARY AT THE SEVENTH GRADE STUDENTS OF SMPN 19 MATARAM IN ACADEMIC YEAR 2016/2017 - Yulia Yulia (Muhammadiyah University of Mataram, 2017)
Line drawing is the draw which can be made in the board directly in the classroom or it can be prepared in certain papers before entering the classroom. The aim of this research was to investigate the use of line drawing has an effect or not in teaching English vocabulary at the seventh-grade students of junior high school. The research was conducted the first semester at the seventh-grade students of SMP Negeri 19 Mataram. The population in this research was the seventh-grade students of SMP Negeri 19 Mataram, in which the total number of the class were five classes and in this research just conducted in two classes. The sampling technique was cluster sampling. The total numbers of the students as sample were 62 students from two classes and each class consist of 31 students. During the period of time, the experimental group was treated by using line drawing and the control group was treated without using line drawing. The result of the research reveals that the mean score of the experimental group is 24.6 and the control group is 12.9. In the other hand, the standard deviation of the experimental group is 2.8 > 1.5 under the identification of t-test formula. It is found that the value of it is 5.62 > 0.05% and 0.01% at the degree of freedom infinitive which is 1.67 and 2.39. From this point, it can be concluded that the alternative hypothesis is accepted or the line drawing has an effect in teaching English vocabulary at the seventh-grade students of SMPN 19 Mataram.